2020
DOI: 10.1016/j.ebiom.2020.103124
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain in children: Steps towards improved recognition and management

Abstract: Neuropathic pain in children can be severe and persistent, difficult to recognise and manage, and associated with significant pain-related disability. Recognition based on clinical history and sensory descriptors is challenging in young children, and screening tools require further validation at older ages. Confirmatory tests can identify the disease or lesion of the somatosensory nervous system resulting in neuropathic pain, but feasibility and interpretation may be influenced by age-and sex-dependent changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 76 publications
0
34
0
5
Order By: Relevance
“…Indeed, the diagnosis of neuropathic pain during VOC raises the problem of fine descriptions of the characteristics of the pain, which are sometimes difficult in young children, especially during an intensely painful episode where many sensations are mixed, including anxiety, fear of parental separation, and adverse effects of treatment (pain related to infusion devices, opioid-induced pruritus or hyperalgesia, etc.). Moreover, the diagnosis between “pure neuropathic” and “mixed pain” in children and adolescents is very difficult for several reasons: We do not dispose of many diagnostic tools, as questionnaires validated for adults and the electrophysiologic methods, such as quantitative sensory testing (QST) or electromyography (EMG), cannot be easily used in children [ 22 , 23 ]. In a recent survey study among members of learned societies or groups whose members are known to treat pediatric pain, de Leeuw et al [ 11 ] observed that only 45.3% of the respondents used the IASP criteria for establishing the diagnosis of neuropathic pain in children, while 18 (15.4%) explicitly answered that they did not use these criteria; 46 persons (39.3%) left this question unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the diagnosis of neuropathic pain during VOC raises the problem of fine descriptions of the characteristics of the pain, which are sometimes difficult in young children, especially during an intensely painful episode where many sensations are mixed, including anxiety, fear of parental separation, and adverse effects of treatment (pain related to infusion devices, opioid-induced pruritus or hyperalgesia, etc.). Moreover, the diagnosis between “pure neuropathic” and “mixed pain” in children and adolescents is very difficult for several reasons: We do not dispose of many diagnostic tools, as questionnaires validated for adults and the electrophysiologic methods, such as quantitative sensory testing (QST) or electromyography (EMG), cannot be easily used in children [ 22 , 23 ]. In a recent survey study among members of learned societies or groups whose members are known to treat pediatric pain, de Leeuw et al [ 11 ] observed that only 45.3% of the respondents used the IASP criteria for establishing the diagnosis of neuropathic pain in children, while 18 (15.4%) explicitly answered that they did not use these criteria; 46 persons (39.3%) left this question unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…Sinir sisteminin hasar görmesiyle nöropatik ağrı ortaya çıkmaktadır. Nöropatik ağrı, dokunma, basınç, ağrı, sıcaklık, titreşim algısını oluşturan somatosensör sistemin hasarlanmasıyla birlikte ortaya çıkan ağrı olarak tanımlanmaktadır (22). Çocuklarda kansere bağlı görülen nöropatik ağrının genel prevelansı bilinmemektedir (10,22).…”
Section: Kemoterapiyle İlişkili Periferik Nöropati Semptomlarıunclassified
“… 83 , 84 Although multiple mechanisms including inflammation and pain arising from muscles, joints, and viscera may also contribute to CPSP, 85 this section will focus on neuropathic pain, because this can be difficult to recognize in children and has specific implications for management. 86 In pediatric studies, there is significant variability in the diagnostic criteria and reported prevalence of neuropathic CPSP (e.g., 10%–89% with CPSP following scoliosis surgery 87–89 ). Outcomes used to support possible or probable neuropathic pain have included history and clinical descriptors, neuropathic screening tool questionnaires, somatosensory testing, conditioned pain modulation, and response to treatment (e.g., topical lidocaine patch) 35 , 87 , 88–91 .…”
Section: Nerve Injury and Neuropathic Cpspmentioning
confidence: 99%
“… 23 Delayed emergence of neuropathic pain has also been reported following traumatic or surgical nerve injury in children. 35 , 86 , 94 The potential for preclinical studies to also link specific sensory modalities and mechanisms to efficacy of pharmacological interventions has been highlighted 95 and warrants further assessment at different developmental stages. In addition, more complex behavioral tasks in adult rodents have evaluated alterations in motivational–affective response (e.g., conditioned place preference, social interaction, anxiety) and cognitive function (e.g., memory and attention) 95–98 and have identified long-term effects following surgical injury in early life (increased anxiety, impaired attentional performance and learning 99 ).…”
Section: Nerve Injury and Neuropathic Cpspmentioning
confidence: 99%